Empowering Metacognition with Mind Map to Optimize the Product Quality of Learning Outcome - Ema Aprilisa (BIOEDUKASI, 2019)
Learning outcome can be one of the reference to rate the success of a learning process. Product, as a result of learning, become an important aspect that can reflect success of learning. This research will proving the importance of metacognition to optimize the quality of learning outcomes. Metacognition is facilitated using mind maps during the learning process. The data in this research were obtained the method of triangulation through the analysis of the results of questionnaires, interviews, and evaluating products as a learning outcome. These three data are then collaborated to show the conclusions about metacognition to optimize the quality of learning outcomes using mind map. This research proved that mind map are able to facilitate metacognition. Metacognition also give affects to learning outcomes, in this case is lesson plan or RPP. Not only proving mind map as a tool to facilitate metacognition, this research also proves if there is a relationship betwen metacognition and achievement of learning outcomes, especially for product as a learning outcome.